Sensory Profiling Evaluation and Panel Performance Test of Chocolate Ice Cream Premix Products - Fransiska Utami; Dede Robiatul Adawiyah; Dias Indrasti (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2023)
The growth of the food and beverage industry in Indonesia is creating new opportunities for the ice cream sector, which experienced a remarkable 51.9% growth between 2013 and 2018. Nowadays, crafting ice cream at home has become convenient through the use of premixes, often added with chocolate flavor. Therefore, this study aimed to conduct a sensory profiling evaluation and panel performance test on chocolate ice cream mix powder products. Sensory analysis was used to analyze product quality, differences, and similarities, with humans as measurement tools. This study also employed a group of trained and reliable panelists for product testing. The sensory profile and performance of several chocolate ice cream premixes on the market were assessed with the quantitative descriptive analysis (QDA) method. The premix products considered were those registered with BPOM, and the analysis encompassed physical characteristics (overrun and melting rate) and sensory evaluation. Meanwhile, the panelist selection was based on ISO 8586 Year 2012. Panelist performance evaluation was conducted to determine their proficiency in sensory analysis, and the results obtained were analyzed using sensehub and XLSTAT. The QDA test results showed that PT XYZ chocolate ice cream premix was superior in all sensory attributes. However, the weaknesses identified in this premix were related to low overrun value and higher melting rate. The panelist performance evaluation indicated that panelists P1 to P9 needed retraining in discrimination skills. This is because although the panelists had a relatively good consistency, their discrimination ability showed insignificant results.